THE FRAGMENTATION THRESHOLD OF PYROCLASTIC ROCKS - Spieler O.; Kennedy B.; Kueppers U.; Dingwell D.B.; Scheu B.; Taddeucci J. (My University, 2004)
In response to rapid decompression, porous magma may fragment explosively. This occurs when the melt can no longer withstand forces exerted upon it due to the overpressure in included bubbles. This occurs at a critical pressure difference between the bubbles and the surrounding magma. In this study we have investigated this pressure threshold necessary for the fragmentation of magma. Here we present the first comprehensive, high temperature experimental quantification of the fragmentation threshold of volcanic rocks varying widely in porosity, permeability, crystallinity, and chemical composition. We exposed samples to increasing pressure differentials in a high temperature shock tube apparatus until fragmentation was initiated. Experimentally, we define the fragmentation threshold as the minimum pressure differential that leads to complete fragmentation of the pressurized porous rock sample. Our results show that the fragmentation threshold is strongly dependent on porosity; high porosity samples fragment at lower pressure differentials than low porosity samples. The fragmentation threshold is inversely proportional to the porosity. Of the other factors, permeability likely affects the fragmentation threshold at high porosity values, whereas chemical composition, crystallinity and bubble size distribution appear to have minor effects. The relationship for fragmentation threshold presented here can be used to predict the minimum pressure differential necessary for the initiation or cessation of the explosive fragmentation of porous magma.
Keywords: Fragmentation; threshold; experimental; volcanology; magma; eruption; porosity; decompression